The Effects of Chasing Productivity Demand on Mental Health and Workplace Cheating Behavior: The Moderating Role of HR Support - Asa Sheila Amelia; Fauzi Ichwani; Rizki Maulana Ahzar; Ekka Nurcahyaningrum; Aruni Maratussolihah (LP2M IAIN Palopo, 2026)
The garment manufacturing industry is characterized by intensive production targets and high work demands, which may adversely affect employee health and workplace behavior. Excessive job demands often increase performance pressure, leading to psychological strain, stress, and declining employee wellbeing. At the same time, organizations are challenged to maintain productivity without compromising employee health. This study aims to examine the effect of job demands on employee health, investigate the mediating role of performance pressure, and analyze the moderating role of human resource support in mitigating the negative consequences of demanding work environments. The study adopts a mixed-methods approach, combining quantitative and qualitative methods. Quantitative data will be collected through questionnaires distributed to employees in the garment manufacturing sector, while qualitative insights will be obtained through in-depth interviews. Data analysis will be conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) and supported by qualitative thematic analysis. The findings are expected to provide empirical evidence regarding the mechanisms through which job demands influence employee health and to demonstrate the buffering role of human resource support in reducing adverse outcomes. This study contributes to the literature on employee wellbeing, job demands, and sustainable human resource management, while offering practical recommendations for organizations seeking to balance productivity goals with employee health and sustainable workplace practices. Unlike previous studies that primarily focused on productivity demand and employee performance, this study simultaneously investigates employees' mental health and workplace cheating behavior while incorporating HR Support as an organizational buffering mechanism.